1986
DOI: 10.1111/j.1528-1157.1986.tb03600.x
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin in the Treatment of Epilepsy: A Double‐Blind, Placebo‐Controlled Study

Abstract: The efficacy and tolerability of vigabatrin (gamma-vinyl GABA, GVG), given as add-on therapy to 23 adult outpatients with severe drug-resistant epilepsy (17 with partial seizures), were studied using a double-blind, placebo-controlled, crossover design. The study consisted of two 7-week periods during which vigabatrin and placebo were administered in random sequence. Dosage was 1.0 g twice daily for patients weighing less than or equal to 65 kg and 1.5 g twice daily for patients weighing greater than 65 kg. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 12 publications
(12 reference statements)
5
62
0
2
Order By: Relevance
“…Excessive glutamate binding to NMDA receptors allows entry of Ca 2+ into the post-synaptic neuron, causing necrotic cell death or apoptosis, whereas the excessive glutamate binding to non-NMDA receptors allows entry of Na + into the post-synaptic neuron, resulting in cytotoxic edema. Because glial cells also have these receptors, excessive glutamate leads to glial cell damage as well [20]. This could have been the underlying mechanism behind the cell loss in the present study too.…”
Section: Discussionmentioning
confidence: 74%
“…Excessive glutamate binding to NMDA receptors allows entry of Ca 2+ into the post-synaptic neuron, causing necrotic cell death or apoptosis, whereas the excessive glutamate binding to non-NMDA receptors allows entry of Na + into the post-synaptic neuron, resulting in cytotoxic edema. Because glial cells also have these receptors, excessive glutamate leads to glial cell damage as well [20]. This could have been the underlying mechanism behind the cell loss in the present study too.…”
Section: Discussionmentioning
confidence: 74%
“…Vigabatrin (-y-vinyl GABA), a specific, enzymeactivated irreversible inhibitor of GABA-transaminase (GABA-T) has been shown to be an effective anti-convulsant agent for complex partial seizures (Gram et al, 1983;Browne et al, 1983;Rimmer & Richens, 1984;Gram et al, 1985;Loiseau et al, 1986;Schechter, 1986;Tartara et al, 1986;Tassinari et al, 1987). In all published studies to date vigabatrin has been administered orally on a twice-daily schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that elevation of brain GABA by this mechanism can prevent experimental seizures (2 1- 23,29), and clinical trials have shown vigabatrin to have beneficial eKects in 'certain types of drug re-sistant or uncontrolled epilepsy (4,8,20,26,31,32).…”
Section: Introductionmentioning
confidence: 99%